From challenges to solutions: Development and evaluation of alumni engagement portal system for tracer studies - Cresencio, Marion A (Journal of Education and e-Learning Research, 2026)
The Alumni Engagement Portal System (AEPS) is a new system at the Polytechnic University of the Philippines, designed to address limited alumni engagement caused by outdated manual methods and inconsistent monitoring. This system was developed through surveys, expert reviews, and pilot testing. A survey validated with Cronbach’s Alpha yielded a score of 0.9236, confirming its high reliability. Pilot testing showed high levels of usability, acceptability, and increased alumni engagement. The system, developed using agile methodology, is recognized for its user-friendly design and data privacy compliance. It integrates functionalities such as tracer studies, networking opportunities, and data analytics for institutional decision-making. Additionally, it provides insights into employment trends, enabling the university to align curricula with industry needs. Overall, AEPS bridges the gap between alumni and the university by offering a centralized, accessible, and interactive portal. The study recommends future development explore artificial intelligence initiatives for predictive analytics and personalized experiences. This portal represents a transformative step in strengthening alumni-institution relationships and significantly contributes to higher education management practices.